Analysis of cyclic performance of stiffened steel plate Shear walls / Analysis of cyclic performance of stiffened steel plate Shear walls / Omid Haddad - Omid , Haddad (2017)
Steel plate shear wall (SPSW) is a structural system, which is used to resist lateral loading such as wind and earthquake. SPSWs consist of a relatively thin steel plate connected to boundary columns and beams. The infill plates can be stiffened or un-stiffened. The main objective of this research is to study the behavior and energy absorption of stiffened SPSW with various configurations of stiffeners under lateral loading. Experimental and numerical methods were deployed to achieve the main objectives. In experimental study, five quarter scale specimens were tested. Two specimens were un-stiffened and, three specimens were stiffened with cross, circular and diagonal stiffeners on one side of steel infill plate. The cross-section areas of stiffeners were kept constant. A comparison of the predicted behavior of five FE model with the experimental test results indicated that the finite element method is able to provide a reliable prediction of the overall behavior of SPSWs subjected to cyclic loading. Using the parametric studies on the FE models, the behavior and sensitivity of cyclic performance to the value of different slenderness of infill plate, thickness of stiffeners and their position on the SPSWs were investigated. It was found that the energy dissipation, seismic performance factors and cyclic performance of stiffened SPSWs were not sensitive to the stiffeners thickness and their configuration. One-side cross-stiffened models and double-side diagonally stiffened models exhibit considerable increases in the strength compared to the un-stiffened infill plate. Furthermore, using the stiffeners resulted in 30% increase in the ductility reduction factor and 20% increase in the response modification factor for stiffened SPSWs.